Clinical utility of cyclosporine (CsA) ophthalmic emulsion 0.05% for symptomatic relief in people with chronic dry eye: a review of the literature - Rhee, Michelle K (Clin Ophthalmol, 2017)
To review the literature on the efficacy of cyclosporine (CsA) ophthalmic emulsion 0.05% on symptomatic relief in chronic dry eye disease. There is consistent evidence of objective improvements in chronic dry eye disease (Schirmer score, corneal and interpalpebral dye staining, and tear breakup time) with CsA, but variable results with symptomatic improvement, possibly due to patient tolerance of CsA, similar comforting effect with artificial tears and CsA vehicle, and the inherent subjective nature of symptom monitoring and analysis. This review explores the literature on CsA with special attention to symptomatic relief.